Integration of Linguistic and Methodological Disciplines as a Factor in Developing the Professional Competence of Future English Language Teachers - Khatamova, Orzikhon (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
The preparation of future English language teachers in contemporary higher education requires a pedagogical model that effectively combines theoretical linguistic knowledge with the methodological expertise necessary for classroom practice. This article examines the integration of linguistic and methodological disciplines within the framework of linguodidactic training, emphasizing their combined influence on the development of professional competence. Such competence encompasses linguistic mastery, methodological skill, and communicative ability, all of which are essential for effective language teaching. Drawing upon the principles of an interdisciplinary approach, the paper highlights the shortcomings of the traditional separation between language theory and pedagogy, argues for a more unified curriculum, and proposes strategies for achieving meaningful integration. The discussion is supported by insights from both theoretical scholarship and practical teacher education experience.